2017
DOI: 10.1016/j.jphys.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

An app with remote support achieves better adherence to home exercise programs than paper handouts in people with musculoskeletal conditions: a randomised trial

Abstract: ACTRN12616000066482. [Lambert TE, Harvey LA, Avdalis C, Chen LW, Jeyalingam S, Pratt CA, Tatum HJ, Bowden JL, Lucas BR (2017) An app with remote support achieves better adherence to home exercise programs than paper handouts in people with musculoskeletal conditions: a randomised trial. Journal of Physiotherapy 63: 161-167].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 27 publications
7
128
0
7
Order By: Relevance
“…which reduced to 52% at week 8, and Conroy et al(3) reported only half of participants adhered to their programme and almost one quarter completed no exercise diaries.Adherence to home-based exercise is affected by factors such as low motivation, pain and past experience of exercise(33). Participants in the active comparator group reported that completing and returning the exercise diaries improved their adherence.…”
mentioning
confidence: 99%
“…which reduced to 52% at week 8, and Conroy et al(3) reported only half of participants adhered to their programme and almost one quarter completed no exercise diaries.Adherence to home-based exercise is affected by factors such as low motivation, pain and past experience of exercise(33). Participants in the active comparator group reported that completing and returning the exercise diaries improved their adherence.…”
mentioning
confidence: 99%
“…With respect to motivation, patients often need extra support (e.g. by a mobile app) 41 to continue exercising. 42 Serious games also have the potential to improve the motivation to exercise, 24,25 but this has mostly been shown in studies lasting only 4-6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, more data is required to thoroughly evaluate this. Motivation to complete independent exercises is a known issue in physiotherapy practice (for both adults and children) and technological supports are showing promising results in improving compliance [18]. The particular value added by an embodied artificial agent such as NAO versus a virtual graphical body (for example, a video or animation) has also been previously explored, with evidence suggesting that participants perceive more social presence when interacting with a robot than with other virtual agents [19,45], which, in turn, may lead to heightened motivation and emotional connection with the aid.…”
Section: Discussionmentioning
confidence: 99%